2011
DOI: 10.1007/978-90-481-2853-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Cholesky Decomposition Techniques in Electronic Structure Theory

Abstract: We review recently developed methods to efficiently utilize the Cholesky decomposition technique in electronic structure calculations. The review starts with a brief introduction to the basics of the Cholesky decomposition technique. Subsequently, examples of applications of the technique to ab inito procedures are presented. The technique is demonstrated to be a special type of a resolution-of-identity or density-fitting scheme. This is followed by explicit examples of the Cholesky techniques used in orbital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 93 publications
2
117
0
Order By: Relevance
“…It has been employed in the iterative updates of plane-wave DFT calculations, 60 where the full Fock matrix is enormous and thus, evaluating a narrow rectangular matrix is far preferable to an enormous square matrix. Indeed, the idea of constructing this economized version of K was mentioned briefly by Aquilante et al, 61 but we have found no prior or subsequent discussion in the literature. The important point that has not yet been accomplished is to demonstrate how formation of an economized K matrix can be used for computational advantage with AO basis sets.…”
Section: A Economization Of the K Matrixmentioning
confidence: 90%
“…It has been employed in the iterative updates of plane-wave DFT calculations, 60 where the full Fock matrix is enormous and thus, evaluating a narrow rectangular matrix is far preferable to an enormous square matrix. Indeed, the idea of constructing this economized version of K was mentioned briefly by Aquilante et al, 61 but we have found no prior or subsequent discussion in the literature. The important point that has not yet been accomplished is to demonstrate how formation of an economized K matrix can be used for computational advantage with AO basis sets.…”
Section: A Economization Of the K Matrixmentioning
confidence: 90%
“…48,49 The cc-pVTZ basis set was used in all FDET calculations except for the bromine model system, where the aug-cc-pVDZ basis set was applied. 50,51 The implementation uses Cholesky-based ab initio density fitting 52 to approximate the two-electron integrals: the required auxiliary basis set is not pre-optimized through data-fitting but it is generated through Cholesky decomposition of each atomic sub-block of the integral matrix. Next to the computational advantage compared to conventional integral calculations, this type of density fitting guarantees to a large extent complete error control in the computed energy 53,54 and energy gradients.…”
Section: Numerical Detailsmentioning
confidence: 99%
“…[187] Calibration of the resulting ABS on small to medium sized complexes with a variety of oxidation states indicates that negligible fitting errors are produced. [185,187,[190][191][192] An alternative to DF using preoptimized ABSs are methods based on Cholesky decomposition (CD) techniques, and although such methods have been the subject of recent reviews, [194,195] they are briefly recapped below. A symmetric positive definite matrix V can be decomposed into the product of a lower triangular matrix, L, and its adjoint:…”
Section: Auxiliary Basis Setsmentioning
confidence: 99%